Impact of maternal use of asthma-controller therapy on perinatal outcomes. Issue 8 (13th April 2013) - Cossette, Benoit; Forget, Amélie; Beauchesne, Marie-France; Rey, Évelyne; Lemière, Catherine; Larivée, Pierre; Battista, Marie-Claude; Blais, Lucie
Abstract : Background: Asthma during pregnancy usually requires treatment with controller medications about which more safety information is needed. The objectives are to assess the impact of the use of long-acting β2 -agonists (LABAs) and the dose of inhaled corticosteroids (ICSs) during pregnancy on the prevalence of low birth weight (LBW), preterm birth (PB) and small for gestational age (SGA). Methods: A cohort of women with asthma giving birth from 1998 to 2008 was constructed from Québec (Canada) administrative databases. LBW was defined as weight <2500 g, PB as delivery before 37 weeks' gestation and SGA as a birth weight below the 10th percentile. The impact of the use of LABAs and the dose of ICSs during pregnancy on the outcomes was determined with generalised-estimating-equation models. Results: The cohort included 7376 pregnancies: 8.8% exposed to LABAs and 56.9% exposed to ICSs. All LABA users also received ICSs. The prevalence of LBW, PB and SGA was 7.7%, 9.5% and 13.5%, respectively. LABA use was not found to be associated with increased prevalence of LBW (OR 0.81; 95% CI 0.58 to 1.12), PB (OR 0.84; 95% CI 0.61 to 1.15) or SGA (OR 0.92; 95% CI 0.70 to 1.20). Mean ICSs doses >125 μg/day (fluticasone-equivalent) were associated with a non-significant trend of increased LBW, PB and SGA. Conclusions: Despite the possibility of residual confounding due to uncontrolled or more severe asthma or smoking status, the use of LABA and low to moderate doses of ICSs were not associated with increased prevalence of perinatal outcomes. Additional research on higher ICSs doses is required to better evaluate their safety during pregnancy.